Contributing Authors and Institutions to the Journal of Finance: 1946-1985 - Heck, J. Louis; Cooley, Philip L.; Hubbard, Carl M. (Journal of Finance, 1986)
Publication of the December 1985 issue of the Journal of Finance completed the Journal's first 40 years of contributions to the profession. This study identifies and summarizes the contributing authors, where they earned their doctoral degrees, and their employers at the time of publication. The authors, degree-granting institutions, and employers appearing most frequently in the Journal are ordered for the entire 40-year period and for various subperiods. Where possible, the present findings are compared with those of previously published studies.